1969
DOI: 10.5006/0010-9312-25.11.445
|View full text |Cite
|
Sign up to set email alerts
|

Protective Films and Structure Dependent Corrosion in Aluminum

Abstract: Specimens of high purity aluminum with a high temperature oxide film, or certain others, were compared in 16% HCl with polished and etched specimens. Pitting attack was initiated only at sites where the film had suffered mechanical damage during cooling. The structure-related distribution of these sites, associated with vacancy condensation voids or grain boundary shearing, could determine the distribution of attack overshadowing the intrinsic effects of substrate structure. The pitting parameters were correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Oxide films are more unstable under these conditions (17,18) and any film (or adsorbed layer) that is present must be different from that on the freely exposed (unpitted) surface. Therefore, the development of {001} facets within pits must be due to lower metal dissolution rates on {001} surfaCes in the concentrated pit solution, consistent with dissolution studies of A1 in chloride-containing acid solutions (7,8).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Oxide films are more unstable under these conditions (17,18) and any film (or adsorbed layer) that is present must be different from that on the freely exposed (unpitted) surface. Therefore, the development of {001} facets within pits must be due to lower metal dissolution rates on {001} surfaCes in the concentrated pit solution, consistent with dissolution studies of A1 in chloride-containing acid solutions (7,8).…”
Section: Discussionsupporting
confidence: 68%
“…Generally, the facets have not been carefully examined crystallographically and were assumed to coincide with {001} planes. Consistent with this, Arora and Metzger (7) found that corrosion of polycrystalline A1 in 16% HC1 solution was greatest on grain surfaces oriented near {111} planes and least on those near {001}. Similar corrosion behavior was observed by Orem (8) aftel' exposing single crystals of A1 to an acid mixture containing HC1, HNO3, and HF.…”
mentioning
confidence: 52%
“…ating the corrosion resistance of a protective layer is the development of a quantitative accelerated corrosion test. Failure of an A1203 protective layer is always initiated at one or more localized defects (5). Thus the corrosion test should be sensitive to these defect sites or weak spots.…”
Section: Corrosion Resistance~a Common Problem In Evalu-mentioning
confidence: 99%